RANCANG BANGUN SISTEM KONTROL ALAT PENYIRAM TANAMAN OTOMATIS BERBASIS IoT YANG MENGGUNAKAN APP BLYNK - Rumalutur, Sonny (LPPM Poltek ST Paul, 2024)
It is hoped that this IoT-based automatic plant watering tool can be developed and help overcome problems in watering plants. Automatic plant waterer using Soil Sensor, Water Pump, NODEMCU ESP8266, BLYNK App, RTC Sensor, Arduino Uno. The data input from the Soil Sensor is connected to the NODEMCU ESP8266 and the data will be sent online and will be monitored on the BLYNK App, the Water Pump is controlled by the RTC Sensor at a predetermined time and controlled manually via the BLYNK App, the NODEMCU ESP8266 as a microcontroller will send data and receive data from the BLYNK App online, the BLYNK App which is an IoT platform that will receive input/output data from the NODEMCU ESP8266, the RTC Sensor provides data input in the form of time on the Arduino Uno microcontroller to control the Water Pump, the Arduino Uno microcontroller which functions to receive data from the Sensor RTC and controls the Water Pump automatically at a predetermined time.